Estimation of Root Canal Working Length Using Three Different Apex Locators, An In-Vitro Study - Ammar Azeaz Lateef; Samer Aun Thyab; Noor Salman Nadhum (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction: The purpose of this study was to compare the accuracy of different generations of electricalapex locators (EALs) using different measuring protocols. The accuracy of E-PEX PRO (Eighteeth,Changzhou, China) as newly introduced device, Root ZX (J Morita Corp, Tokyo, Japan), and iPex (NSK,Tochigi, Japan) EALs were evaluated.Methods: In this study thirty extracted human permanent single rooted premolar were used. The workinglength was determined with #15 K-file, then by one of the three EALs, first by introducing the file into thecanal until the EAL reads 0.0 then retracting the file until it reads +1.0, second by proceeding the file until theEAL reads +1.0. The data were analyzed using One-way repeated measure ANOVA test at P value of (0.05).Results: No statistically significant differences were found between the three EALs at either measuringprotocolConclusions: Under the in-vitro conditions of the current study, all tested EALs were accurate in estimatingworking length.